Ofloxacin‐loaded HMPB NPs for Klebsiella pneumoniae eradication in the surgical wound with the combination of PTT. Issue 7 (9th April 2022) - Liu, Tiansheng; Zhong, Guowei; Tang, Dongying; Liu, Xu; Fan, Jialong; Zhong, Xianghua; Yang, Yuejun; Tong, Chunyi; Liu, Bin; Yang, Xiaoping
Abstract: Klebsiella pneumoniae (K. pneumoniae) is a common bacterium whose drug‐resistant can cause surgical failures and incurable infections in hospital patients. Thus, how to reverse or delay the resistance induction has become a great challenge for development antiresistant drug. Recently, the combination of nanomaterial‐loaded antibiotics with photothermal therapy showed the efficient antibacteria ability under a low dosage of antibiotics. In this study, a nanocomposite of HMPB NPs with inherent photothermal therapy capability was used to eradicate K. pneumoniae after loading with Ofloxacin, an antibiotic against K. pneumoniae in vitro and in vivo. The nanocomplexes named as Ofloxacin@HMPB@HA NPs showed a higher effect against K. pneumoniae by destroying cell integrity and inducing ATP leakage with the assistance of laser irradiation, compared with sole Ofloxacin@HMPB@HA NPs or laser irradiation. Surgical wound infection assay further demonstrated the efficient killing K. pneumoniae and promoting the formation of new tissues, as well, which was reflected by the rapid healing of surgical wound. In summary, these results indicate the great potential of this combinational tactic based on Ofloxacin@HMPB@HA NPs for preventing the failure caused by K. pneumoniae infection. Abstract : A nano‐antibiotic based on the Prussian blue nano‐platform realizes the combination of antibiotics and photothermal therapy, which not only has an efficient bactericidal effect and reduces bacterial resistance but also achieves rapid healing of surgical wounds in vivo.